Peningkatan Hasil Belajar Siswa Menggunakan Model Pembelajaran Numbered Heads Together pada Tematik Terpadu Sekolah Dasar - Yasni Febri; Mansurdin Mansurdin (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The research used was Classroom Action Research (CAR). The purpose of this study was to describe the increase in student learning outcomes in integrated thematic learning using the Role Playing learning model in class IV SD Negeri 32 Air Amo Sijunjung distrits. The research subjectswere teachers (practitioners) and 17 students. The research location is SD Negeri 32 Air Amo Sijunjung distrits . The results showed an increase in: a) RPP observation of the first cycle was 82,5%,(B)  the second cycle was 87.5% (B); b) Observation aspect of the first cycle teacher is 81,25%(C), the second cycle is 93, 75% (A); c) Observation aspects of the student's first cycle is 79,68% (C)and the second cycle is 93.75% (A); d) learning outcomes in the first cycle are 71,66 (D) and the second cycle is 77, 67 (C).